Pengaruh ROA, ROE, EPS Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Industri Semen Di Bursa Efek Indonesia - Darmawan, Rizky Lazuardi; Megawati, Liya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The construction and building industry sector has an important role in the development of the country's economy because it affects most economic sectors and industries in the country which is an important contributor to the infrastructure development process in providing a physical foundation on which development efforts and improving living standards can be realized. Adaoun one of them uses financial statement analysis involving financial ratios as a measuring tool, such as Return On Equity (ROE), Return On Assets (ROA) and Earning Per Share that can be considered for investment purposes. The purpose of this study was to analyze how much influence ROE, ROA, and EPS both partially and simultaneously on the stock price in the Construction and Building Industry Sub-Sector Companies listed on the Stock Exchange in the period 2016-2020. The analytical method used is quantitative analysis verification. The data was tested using SPSS v.16 with multiple linear regression analysis tests, coeficient determination, hypothesis testing that tested its validity through normality tests, multicollinearity tests, and autocorrelation tests. The sample is selected using the purposive sampling method. The results showed that some ROA and ROE variables had a significant effect on stock prices while other variables such as EPS did not have a significant effect. Simultaneous test results, namely ROE, ROA, and EPS together have an insignificant effect on stock prices.